Morphology of Dorsal Venous Arch of Hand: A Cadaveric Study - Tiwari, Nripendra; Budhathoki, Deepesh; Shrestha, Iju; Timsina, Ram; Shah, Santosh Kumar; Malla, Banshi Krishna (Journal of College of Medical Sciences-Nepal, 2019)
Background: Venous network of hand is superficially placed and is easy to trace for clinical purposes. Ce-phalic vein on lateral aspect and basilic vein on medial aspect of the hand are clinically important for inva-sive and surgical procedures. Thus the study of cephalic and basilic veins at dorsal venous arch of hand was dissected to observe for length of dorsal venous arch and the diameter and thickness of cephalic and basilic veins. Methods: This is a cross-sectional observational study conducted in 50 hands of cadavers (36 hands of male cadavers, 14 hands of female cadavers) in Department of Anatomy, Kathmandu Medical College Teaching Hospital, Duwakot. Cadavers were performed to measure the length of dorsal venous arch, diame-ter and thickness of cephalic and basilic vein on dorsum of hands. Results: The mean±s.d. length of dorsal venous arch in male cadaver (19.03±2.84 cm.) was significantly greater than in female (16.51±1.36 cm.).There was no significant difference in length of dorsal venous arch on right (18.22 ±2.47 cm.) and left side (18.42±3.05 cm.) in either sex. The mean±s.d thickness of basilic vein (0.10±0.01mm) in either sex was significantly greater than that of cephalic vein (0.09±0.01mm). Conclusions: The length of the dorsal ve-nous arch in male cadavers was found significantly greater than in female cadavers. The diameters based on external and internal circumference of basilic veins was found to be more than diameter of cephalic veins in both male and female cadavers. The thickness of basilic vein was found to be more (0.10±0.01mm) than that of cephalic vein (0.09±0.01mm) in cadaver of both sexes.